2008
DOI: 10.1016/j.jpcs.2007.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced phase transformations in l-alanine crystals

Abstract: Raman scattering and synchrotron X-ray diffraction have been used to investigate the highpressure behavior of L-alanine. This study has confirmed a structural phase transition observed by Raman scattering at 2.3 GPa and identified it as a change from orthorhombic to tetragonal structure. Another phase transformation from tetragonal to monoclinic structure has been observed at about 9 GPa. From the equation of state, the zero-pressure bulk modulus and its pressure derivative have been determined as (31.5±1.4) G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 25 publications
3
29
0
Order By: Relevance
“…The tetragonal phase is stable up to 9 GPa, when L-alanine-h 7 undergoes a second structural phase transition to a monoclinic symmetry. [17] In the present work we found changes at ∼1.5 GPa and at ∼4.4 GPa, i.e. pressure values well below those observed for L-alanine-h 7 .…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The tetragonal phase is stable up to 9 GPa, when L-alanine-h 7 undergoes a second structural phase transition to a monoclinic symmetry. [17] In the present work we found changes at ∼1.5 GPa and at ∼4.4 GPa, i.e. pressure values well below those observed for L-alanine-h 7 .…”
Section: Discussionsupporting
confidence: 53%
“…At room conditions the crystals of L-alanine are orthorhombic (space group P2 1 2 1 2 1 ) with four zwitterionic molecules per unit cell linked by three networks of hydrogen bonds. [1 -5] L-alanine has attracted the curiosity of many researchers due to (i) a negative thermal expansion along the c-axis, with contraction of the cell volume over the temperature range 2-300 K, as was observed both for glycine [6] and L-serine [7] ; (ii) unusual features in the lattice dynamics of crystal, as a result of localization of vibrational energy [8] ; (iii) anomalies in the region 170-220 K, observed through several experimental measurements, including phonon-echo, dielectric permittivity and NMR [9 -15] and (iv) under high-pressure conditions the crystal undergoes structural phase transitions from orthorhombic to tetragonal and, then, to a monoclinic structure, as shown by Raman [16] and X-ray synchrotron diffraction [17] experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Such modes have also an intriguing behavior with high pressure conditions: between 0 and 2.3 GPa the lowest wavenumber band increases intensity while the band at 49 cm -1 decreases; above the critical pressure of 2.3 GPa, an inverse effect is observed, e.g., the lowest wavenumber band decreases in intensity while the other band increases its intensity (Teixeira et al, 2000). Beyond this, under the scrutiny of the behavior of lattice modes of L-alanine through Raman spectroscopy it was reported the evidence of a structural phase transition at ~ 2.3 GPa (Teixeira et al, 2000), that seems to be confirmed by X-ray diffraction measurements (Olsen et al, 2008). However, very recent works reinterpreted X-ray diffraction measurements as conformational changes of the ammonia group (Funnel et al, 2010;Tumanov et al, 2010).…”
mentioning
confidence: 82%
“…Additionally, (i) the Raman scattering data were not correlated with a structural phase transition, only with continuous changes in the intermolecular interactions (Tumanov et al, 2010); (ii) at about 2 GPa the cell parameters a and b become accidentally equal to each other (Funnel et al, 2010;Tumanov et al, 2010), but maintaining the same orthorhombic structure (P2 1 2 1 2 1 ), differently from the work of ref. (Olsen et al, 2008) that interpreted the X-ray diffraction results as an orthorhombic  tetragonal phase transition. There are three other aliphatic amino acids, which were investigated by Raman spectroscopy under high pressure conditions: L-leucine, L-isoleucine and L-valine.…”
mentioning
confidence: 99%
“…Under high pressure, L-alanine also shows intriguing aspects. For instance, Raman spectroscopy studies have indicated the occurrence of a phase transition at ~ 2.3 GPa [17], which was later confirmed by X-ray diffraction measurements [18]. A new interpretation, however, has indicated that the modifications about 2 GPa might also be understood as a conformation change of the NH 3 + group [19,20].…”
Section: Structural and Vibrational Anomalies Observed In Selected Ammentioning
confidence: 93%